2011
DOI: 10.1007/s10236-011-0407-6
|View full text |Cite
|
Sign up to set email alerts
|

Mixed layer depth (MLD) variability in the southern Bay of Biscay. Deepening of winter MLDs concurrent with generalized upper water warming trends?

Abstract: Mixed layer depth (MLD) variability from seasonal to decadal time scales in the Bay of Biscay is studied in this work. A hydrographic time series running since 1991 in the study area, a climatology of the upper layer vertical structure based on the topology of this temperature profile time series and a onedimensional water column model have been used for this purpose. The prevailing factors driving MLD variability have been determined with detail, and agreement with observations is achieved. Tests carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 47 publications
2
25
0
Order By: Relevance
“…when heat loss is concentrated in intense mixing events, rather than distributed evenly but more weakly throughout the winter (Marshall & Schott, 1999;Somavilla et al, 2011;Våge et al, 2008). Thus, changes in the maximum heat loss registered every winter and in the number of heat loss events higher than the particular threshold defining strong heat loss events are also investigated.…”
Section: Changes In Air-sea Heat Exchangessupporting
confidence: 52%
See 2 more Smart Citations
“…when heat loss is concentrated in intense mixing events, rather than distributed evenly but more weakly throughout the winter (Marshall & Schott, 1999;Somavilla et al, 2011;Våge et al, 2008). Thus, changes in the maximum heat loss registered every winter and in the number of heat loss events higher than the particular threshold defining strong heat loss events are also investigated.…”
Section: Changes In Air-sea Heat Exchangessupporting
confidence: 52%
“…convection episodes appear more likely to occur when the heat loss is concentrated in intense mixing events (Marshall & Schott, 1999;Somavilla et al, 2011;Våge et al, 2008). This could have been the case before the 1980s, thereby explaining the deeper d nb than h. After the 1980s, this could raise the question of whether our approach may be overlooking some intense mixing events that could have penetrated the dome.…”
Section: 1029/2018jc014249mentioning
confidence: 99%
See 1 more Smart Citation
“…A first driver potentially explaining deeper mixed layer depth for some years is the mechanical energy input (e.g. Duhaut and Straub, 2006;Huang et al, 2006;Elipot and Gille, 2009) related with the wind stress and the surface ocean velocity (the surface ocean velocity effect is generally smaller than The alternative source of convective processes deepening the mixed layer depth in winter is the heat fluxes (mostly latent and sensible heat fluxes in winter in the region following Somavilla et al, 2011). During the simulated period, the extremely cold and dry winter in 2005 (Somavilla et al, , 2011(Somavilla et al, , 2016 explains the deepest average mixed layer depth over the domain.…”
Section: Discussionmentioning
confidence: 99%
“…Behrenfeld et al (2006) suggested a general trend has occurred of decreased convective mixing, increased stratification and consequent decrease in production in the Northeast Atlantic from 1999 onwards and predicts a decrease in productivity in a warming ocean. There has been a progressive warming of surface waters in the Bay of Biscay over the last 30 years (Garcia-Soto et al 2002, Somavilla et al, 2011Holt et al 2012;Taboada & Anadon, 2012, Garcia-Soto & Pingree, 2012. Winter mixing was studied extensively in Pingree & New (1989).…”
Section: Introductionmentioning
confidence: 99%